Using social media in new food ventures: the case of Madani & Co+ - Zulkifli, Izyani; Khalid, Haliyana; Md Hanipah, Fadzleen; Wan Yahya, Wan Yusniza (Azman Hashim International Business School, UTM, 2022)
The Malaysian food and beverage industry is one of the major contributors to the national economy. The rapid development of the industry has led to many product innovations in the market. New ventures in the F&B industry often leverage social media platforms to promote their products and services. Studies in the past have captured mixed findings on the effectiveness of the social media platform as a promotional tool. While many have succeeded, there are also cases that did not achieve favourable results. When it comes to social media marketing, different products cater to different audiences, and therefore, require different tactics and strategies. Thus, this research allows for more exploration, especially for new ventures in the F&B industry.